Factors That Affect Body Mass Index of Adults - Asil, Esma; Surucuoglu, Metin Saip; Cakiroglu, Funda Pinar; Ucar, Asli; Ozcelik, Ayse Ozfer; Yilmaz, Mustafa Volkan; Akan, Lale Sariye (Pakistan Journal of Nutrition, 2014)
The aim of the study is to determine the factors that contribute to the body mass index (BMI) of adults and evaluate the eating habits of the individuals. The study was conducted on 498 adults whose ages were ranging from 20 to 85 (39.1±14.9 year). The data were collected using a questionnaire form that consisted of questions concerning general characteristics of individuals, frequency of food consumption and eating habits. Food types in the food consumption frequency were grouped together according to Nutrition Guide for Turkey. Body weights and heights of the individuals were measured. BMI of the 55% of the individuals participated in the study is 25 or higher than 25. The average BMI of the individuals differs according to age, educational, marital, smoking status, parity and sleep duration (p